Strategi Komunikasi Islam Generasi Z dalam Mengelola Identitas Diri - Pratama, Aldyas Wiand (Journal of Islamic Communication Studies, 2025)
The advancement of social media has transformed the ways in which Generation Z constructs and displays self-identity in digital spaces. This study stems from academic concerns surrounding the rising use of private accounts as a form of Islamic communication strategy among young people to balance the need for self-expression with the desire to maintain privacy. This research aims to understand the meaning behind the use of private Instagram accounts for Generation Z and the strategies they employ in managing their self-identity. A qualitative method with a phenomenological approach was used, involving in-depth interviews with several informants aged 20–24 who actively use private Instagram accounts. The findings reveal that private accounts are perceived not merely as a form of data protection, but as a safe space to express a more honest and emotional side of oneself. Generation Z employs strategies such as audience selection, content regulation, and the use of features like close friends and archives to demonstrate communication practices aligned with Islamic communication values. Their ways of limiting access, evaluating the appropriateness of information, and maintaining politeness in sharing posts reflect the principles of caution (tatsabbut), safeguarding personal dignity (hifz al-‘ird), and avoiding potential harm (mudarat) from excessive openness. The use of private accounts shows that Generation Z is not only aware of digital security but also practices Islamic ethical communication in shaping their self-identity on social media.